Analisis Perbandingan Kinerja Keuangan Melalui Pendekatan Ratio Likuiditas Pada PT BNI (Persero) Tbk dengan PT.BRI (Persero) Tbk - Deby Fitri Pujiarti; Nurhayati Nurhayati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The economic progress of a country is greatly influenced by economic activity in the country. All activities are the driving force of economic activity which is very important role. One example of Indonesia's development is in the banking sector. As we know, almost all sectors related to various financial activities always require bank services. The study aims to analyze the financial performance of Bank Negara Indonesia (Persero) Tbk with Bank Rakyat Indonesia (Persero) Tbk. This study uses a Liquidity Ratio analysis method with a Loan to Deposit Ratio (LDR) and Paired Simple. The results showed no significant difference in the LDR ratio at PT Bank Negara Indonesia (Persero) Tbk with the LDR ratio at PT. Bank Rakyat Indonesia (Persero) Tbk